Scalp Metastasis of Gastro-Esophageal Junction Adenocarcinoma: A Rare Occurrence - Roy, Asitava Deb (JCDR Research and Publications (P) Limited, 2014)
Cutaneous metastasis is one of the many skin changes which are associated with internal malignancies. Breast, lung, and colon are the most common sources of internal primary malignancies. Gastro-esophageal junction adenocarcinoma is a rare cause of cutaneous metastasis to the scalp. Gastric adenocarcinoma usually metastasizes to the liver, peritoneal cavity and regional lymph nodes more often than to skin. We are presenting a case of cutaneous metastasis on the scalp of a 79-year-old man, who was diagnosed and operated for gastro-oesophageal junction adenocarcinoma one year back.